Pertanggungjawaban PPAT Atas Keterangan Palsu Dalam Pembuatan Akta Jual Beli Tanah (DiH: Jurnal Ilmu Hukum, 2022)
Land Deed Official has the authority to make the deed relating to land based on Article 1 Paragraph (1) of government regulation of the Republic of Indonesia number 24 of 2016. Land Deed Official should apply the precautionary principle as has been said in the oath of office. In practice, there are many legal problems of Land Deed Official deeds caused by client dishonesty related to the correctness of administrative conditions that cause losses for others. The purpose of this study is to determine the form of accountability for the Land Deed Official top of his negligence in making the deed of sale of land based on false information. This research using the method of juridical normative. The result of this research is if it is proved the deed of sale of land made by Land Deed Official based on false information can be categorized as a violation of the restrictions or obligations which are listed in Appendix II of Regulation of the Ministry of Agrarian Affairs and Spatial Planning/head of the National Land Agency Number 2 of 2018 and Land Deed Official can be held administratively liable, namely dismissed with disrespect under Article 13 regulation of the Ministry of Agrarian Affairs and Spatial Planning/head of the National Land Agency Number 2 of 2018. If based on a court ruling that has permanent legal force (inkracht), the deed made should have the perfect legal force into a deed under the hands then Land Deed Official can be civilly responsible in the form of reimbursement, compensation and interest if the deed causes harm to one of the parties and Land Deed Official may also be subject to criminal liability if it is proved by intentionally or knowingly cooperate with the client to make the deed of sale of land based on false information. Keywords: accountability; false information; land deed official Abstrak Pejabat Pembuat Akta Tanah (PPAT) mempunyai kewenangan membuat akta yang berkaitan dengan pertanahan berdasarkan Pasal 1 ayat (1) PP No. 24/2016. Dalam menjalankan jabatannya, PPAT harus menerapkan prinsip kehati-hatian sebagaimana yang telah diucapkannya pada sumpah jabatan. Pada praktiknya, terdapat banyak permasalahan hukum akta PPAT yang disebabkan adanya ketidakjujuran klien terkait kebenaran syarat administrasi yang menyebabkan kerugian bagi pihak lain. Tujuan dari penelitian ini yaitu untuk mengetahui bentuk pertanggungjawaban bagi PPAT atas kelalaiannya dalam membuat akta jual beli tanah berdasarkan keterangan palsu. Penelitian ini menggunakan metode yuridis normatif. Hasil dari penelitian ini adalah jika terbukti akta jual beli tanah yang dibuat oleh PPAT berdasarkan keterangan palsu dapat dikategorikan sebagai pelanggaran berat terhadap larangan atau kewajiban yang tercantum dalam Lampiran II Permen ATR/BPN No. 2/2018 dan PPAT tersebut dapat dimintai pertanggungjawaban secara administrasi yakni diberhentikan dengan tidak hormat berdasarkan pasal 13 Permen ATR/BPN No. 2/2018. Jika berdasarkan putusan pengadilan yang mempunyai kekuatan hukum yang tetap (inkracht), akta yang dibuat seharusnya memiliki kekuatan hukum yang sempurna menjadi akta dibawah tangan maka PPAT dapat bertanggung jawab secara perdata dalam bentuk penggantian biaya, ganti rugi dan bunga apabila akta tersebut menimbulkan kerugian bagi salah satu pihak dan PPAT dapat pula dikenai pertanggungjawaban pidana jika terbukti dengan sengaja atau disadari bekerja sama dengan klien untuk membuat akta jual beli tanah berdasarkan keterangan palsu. Kata kunci: keterangan palsu; pertanggungjawaban; PPAT